Integrasi Pustakawan Menuju Masyarakat Informasi : Suatu Perspektif Sosial Budaya - LAWANDA, Ike Iswary (Sagung Seto, 2015)
Integrasi Pustakawan Menuju Masyarakat Informasi : Suatu Perspektif Sosial Budaya